2017
DOI: 10.1177/0141076817700848
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between mentoring and doctors’ health and wellbeing: a narrative review

Abstract: (2017) Exploring the relationship between mentoring and doctors' health and well-being: A systematic narrative review. Journal of the Royal Society of Medicine, 110 (5 Northumbria University has developed Northumbria Research Link (NRL) to enable users to access the University's research output. Copyright © and moral rights for items on NRL are retained by the individual author(s) and/or other copyright owners. Single copies of full items can be reproduced, displayed or performed, and given to third parties i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
0
26
0
1
Order By: Relevance
“…While prior reviews have addressed mentoring among physicians, junior doctors, and medical students, there has, to date, been no explicit systematic review of peer mentoring among medical residents [ 35 38 ]. Our review will address an important gap in the literature by comprehensively assessing the impact that peer mentors can have on reducing burnout, enhancing overall emotional wellbeing, and furthering the development of professional competencies in medical residency education.…”
Section: Introductionmentioning
confidence: 99%
“…While prior reviews have addressed mentoring among physicians, junior doctors, and medical students, there has, to date, been no explicit systematic review of peer mentoring among medical residents [ 35 38 ]. Our review will address an important gap in the literature by comprehensively assessing the impact that peer mentors can have on reducing burnout, enhancing overall emotional wellbeing, and furthering the development of professional competencies in medical residency education.…”
Section: Introductionmentioning
confidence: 99%
“…5,14 While our review aligns with previous research reporting on the benefits of mentorship in medical education, it is unique in its focus on the role of peer mentors in developing interpersonal and coping skills, and academic and career competencies among medical residents. 12,15,23,42 A culture of supportiveness amongst peers in medical residency may help to address the psychosocial needs of medical residents as they transition to new roles, and increasingly challenging learning environments. 11 Recent developments in medical education have emphasized the importance of medical residents cultivating soft skills throughout their training.…”
Section: Discussionmentioning
confidence: 99%
“…9,17 Researchers who have studied peer mentorship in graduate education and among healthcare professionals in workplace settings have found that peer mentoring increases socialization and reduces symptoms of burnout. 14,[18][19][20][21][22][23] In a randomized controlled study of the impact of a peer support group program for healthcare workers, Peterson et al reported that "statistically significant intervention effects were found for general health, [and] perceived quantitative demands at work". 22 Other researchers have also noted that increased social or emotional support were associated with decreased burnout among college students and social workers.…”
Section: Introductionmentioning
confidence: 99%
“…The findings were that mentoring positively influenced collegiate relationships, networking and aspects of personal wellbeing, such as confidence and stress management, and was valued by doctors as a specialist support mechanism for professional practice. 12 Ackroyd and Adamson in 2015 published a review paper on 'Mentoring for new consultants' to popularise their mentoring scheme at the Royal College of Physicians of Edinburgh. 13 They suggested that mentees acquired increased job satisfaction, greater self-confidence, improved objectivity with problem solving and ability to implement change, and importantly improved work-life balance.…”
Section: The Grow Methodsmentioning
confidence: 99%